2015
DOI: 10.1007/s11356-015-4569-5
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological and antioxidant traits of Salvia officinalis under ozone stress

Abstract: Ecophysiological and antioxidant traits were evaluated in sage (Salvia officinalis) plants exposed to 120 ppb of ozone for 90 consecutive days (5 h day(-1)). At the end of fumigation, plants showed slight leaf yellowing that could be considered the first visual symptom of leaf senescence. Ozone-stressed leaves showed (1) reduced photosynthetic activity (-70 % at the end of exposure), (2) chlorophyll loss (-59 and -56 % of chlorophyll a and b concentrations, starting from 30 days from the beginning of exposure)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 54 publications
3
26
1
Order By: Relevance
“…Because CO 2 is the final acceptor in the electron transport chain, an inhibition of photosynthetic rate could be expected to affect the redox state of the PSII electron acceptor Q A . In AA plants, we found that there were no changes in the maximal efficiency of PSII photochemistry, similarly to other studies (Ismail et al 2014;Pellegrini et al 2015). This result confirms that ambient O 3 inhibits the ability of olive trees to utilize light energy used in photochemistry (as supported by the alteration in the other parameters such as Φ PSII and qP) but does not change dark reactions of the photosynthetic process (unchanged F v /F m ).…”
Section: Discussionsupporting
confidence: 90%
“…Because CO 2 is the final acceptor in the electron transport chain, an inhibition of photosynthetic rate could be expected to affect the redox state of the PSII electron acceptor Q A . In AA plants, we found that there were no changes in the maximal efficiency of PSII photochemistry, similarly to other studies (Ismail et al 2014;Pellegrini et al 2015). This result confirms that ambient O 3 inhibits the ability of olive trees to utilize light energy used in photochemistry (as supported by the alteration in the other parameters such as Φ PSII and qP) but does not change dark reactions of the photosynthetic process (unchanged F v /F m ).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, DEPS did not change, and this suggests that xanthophyll cycle was not activated. Thus, the tentatively repair or acclimation mechanisms shown by Piedmont plants at the end of the exposure (in terms of mesophyll CO2 fixation ability and qP) could be provided by some antioxidant defense systems, in order to alleviate the excess of excitation pressure (Pellegrini et al 2015b). At the chloroplast level, an important antioxidant role is played by β-carotene (Castagna et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the unchanged chlorophyll concentrations observed in this provenance. However, lowered O3 levels 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 11 incoming into the leaves leaded to a significant decrease of qP reducing the capacity for reoxidizing QA during actinic illumination (Pellegrini et al 2015b). Furthermore, the reduction of ΦPSII suggests that there was a tendency to reduce the light energy used in photochemistry at the expense of the capacity to dissipate the excess of excitation energy, as indicated by the higher values of qNP after 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in AA + 120 plants the C i increment seemed to be mainly due to a diffusional issue, although also a biochemical one could has occurred since a slight decrease in V cmax was observed (J max and TPU were not affected). However, reductions of A sat might also be ascribable to impairments of efficiency of PSII photochemistry (reduced F v '/F m ' and PSII ) and a reduced capacity for reoxidizing Q A during actinic illumination (reduced qP, Pellegrini et al, 2015). This outcome was also confirmed by decreased %P.…”
Section: Discussionmentioning
confidence: 91%